Finite element analysis of free vibration of rectangular composite plates - Tay, Leroy Shi Han (Nanyang Technological University, 2024)
This report presents a comprehensive investigation into the free vibration characteristics of rectangular composite plates using finite element analysis (FEA). The goal of the research is to better understand these structures' dynamic behavior, which is essential for improving their design and guaranteeing structural integrity in a range of technical applications. A three-dimensional thin laminated shell finite element model is developed and implemented as part of the study technique, considering the anisotropic character of composite materials. To investigate the effects of important parameters on the natural frequencies and mode forms of the composite plates, including plate dimensions, stacking order, and material properties, parametric research is carried out. The vibrational response of rectangular composite plates is influenced by a complex interaction of geometric and material parameters, as demonstrated by the results of the finite element analysis. Furthermore, the distribution of nodal patterns and deformation modes is revealed by the modal analysis, which helps identify crucial places that may experience resonance and eventual failure. Moreover, analytical solutions, experimental data, and FEA predictions are compared to verify the precision and dependability of the created finite element model. The results of this study make a significant contribution to the field of composite plate dynamics and provide insightful advice to engineers and designers who aim to improve the longevity and performance of structures made of composite materials. In a nutshell, this study's result emphasizes the value of using finite element analysis to thoroughly examine the properties of free vibration in rectangular composite plates. The knowledge gained serves to support the continuous efforts to optimize composite structures, guaranteeing their effective use in a variety of engineering applications.